2021
DOI: 10.1111/1365-2745.13638
|View full text |Cite
|
Sign up to set email alerts
|

Weather and distance to fire refugia limit landscape‐level occurrence of fungal disease in an exotic annual grass

Abstract: The enemy release hypothesis proposes that invasion by exotic plant species is driven by their release from natural enemies (i.e. herbivores and pathogens) in their introduced ranges. However, in many cases, natural enemies, which may be introduced or managed to regulate invasive species, may fail to impact target host populations. Landscape heterogeneity, which can affect both the population dynamics of the pathogen and the susceptibility and the density of hosts, may contribute to why pathogens fail to contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 77 publications
(102 reference statements)
0
3
0
Order By: Relevance
“…Smuts that are often asymptomatic, living endophytically or in soils may have little year‐to‐year impact on grass productivity and reproduction (Zuo et al., 2019), yet when an outbreak occurs, their impact on the population and future generations are likely exponentially significant to future population dynamics (Farrell et al., 2002). Similarly, smut outbreaks of Ustilago bullata on Bromus tectorum followed weather patterns and landscape characteristics following fires that shifted disease incidence (Applestein et al., 2021). Our study showed similar associations with shifts from wet to dry periods.…”
Section: Discussionmentioning
confidence: 99%
“…Smuts that are often asymptomatic, living endophytically or in soils may have little year‐to‐year impact on grass productivity and reproduction (Zuo et al., 2019), yet when an outbreak occurs, their impact on the population and future generations are likely exponentially significant to future population dynamics (Farrell et al., 2002). Similarly, smut outbreaks of Ustilago bullata on Bromus tectorum followed weather patterns and landscape characteristics following fires that shifted disease incidence (Applestein et al., 2021). Our study showed similar associations with shifts from wet to dry periods.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, fires at the very end and beginning of the year (i.e., winter) were associated with lower smut incidence in plants than prescribed fires that were implemented as the year progressed (through summer). This pattern could have resulted from variation in fire intensity or interactions between weather conditions and plant or pathogen phenology (Mims and Mims, 2004; Applestein et al, 2021), which vary between seasons. For example, it is possible that after prescribed fires early in the year, plants began to form stigma (the suspected location of penetration) while soil temperatures or environmental conditions were not conducive for teliospore germination.…”
Section: Discussionmentioning
confidence: 99%
“…Disturbances have been shown to alter the relationship between fungi and their host plants. Fires, in particular, can alter or reorganize microbial communities as a result of nutrient releases into the soil or changes in vegetation composition or structure (Semenova‐Nelsen et al, 2019; Applestein et al, 2021; Bowd et al, 2021, Vermeire et al, 2021; Hopkins et al, 2023). In addition, research has also shown that fires can cause spores to be released and dispersed long distances via smoke (e.g., Fox et al, 2022).…”
Section: Discussionmentioning
confidence: 99%